Emissões otoacústicas e sistema olivococlear medial: pacientes com zumbido sem perda auditiva - Mor, Rita [UNIFESP] (2005)
BACKGROUND: tinnitus. AIM: to compare the results of otoacoustic emissions for transitory stimulus (TEOAE) and the functioning of the olivocochlear medial system, in individuals with normal hearing sensibility, with and without tinnitus. METHOD: participants of this study were 60 subjects, with tonal thresholds and acoustic imitance measurements within normal standards, distributed in two groups: group one - 30 subjects with tinnitus and group two - 30 subjects without tinnitus, paired up by gender and age. Both groups were submitted to the TEOAE test, with and without the presence of white contralateral white noise at 60dB NPS. For the 19 subjects who presented unilateral tinnitus, TEOAE and suppression results were compared regarding the variables of side, taking in consideration the presence of tinnitus. RESULTS: in the group comparison, with and without tinnitus, there was no significant statistical difference for the incidence of TEOAE, response levels, and incidence of the suppression effect. Significant statistical difference was not observed between the right and left ears in the group with tinnitus. For the 19 subjects with unilateral tinnitus, a higher amplitude of the responses and a higher suppression incidence were observed for the right ear, as well as a higher incidence of tinnitus and a lower incidence of suppression for the left ear. CONCLUSION: there was no significant statistical difference for both TEOAE incidence and response levels, as well as for the functioning of the olivocochlear medial system between the subjects, with normal hearing sensibility, with and without tinnitus. For the subjects who presented unilateral tinnitus, the overall TEOAE reponse levels was significantly higher in the ear with no tinnitus and the olivocochlear medial system was significantly less efficient in the ear with tinnitus.